2015
DOI: 10.1093/annonc/mdv027
|View full text |Cite
|
Sign up to set email alerts
|

A phase 3 randomized, double-blind, placebo-controlled trial of ganitumab or placebo in combination with gemcitabine as first-line therapy for metastatic adenocarcinoma of the pancreas: the GAMMA trial

Abstract: ClinicalTrials.gov NCT01231347.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
79
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(80 citation statements)
references
References 23 publications
0
79
0
1
Order By: Relevance
“…However, many clinical trials with IGF-1R inhibitors failed to show any significant clinical benefit including hepatocellular carcinoma [25], non-small cell lung cancer [26] and breast cancer [27]. In pancreatic cancer, the combination of gemcitabine and ganitumab, a monoclonal antibody against IGF-1R, showed a significant clinical response in a phase 2 randomized trial [28], but unfortunately this combination did not show any clinical benefit in phase 3 evaluation [29]. Recently, a clinical study demonstrated a correlation between IGF-1R signaling and tumor aggressiveness in PDAC patients [15], and increased exposure to ganitumab was found to be associated with improved overall survival and progression free survival in metastatic PDAC [30].…”
Section: Introductionmentioning
confidence: 99%
“…However, many clinical trials with IGF-1R inhibitors failed to show any significant clinical benefit including hepatocellular carcinoma [25], non-small cell lung cancer [26] and breast cancer [27]. In pancreatic cancer, the combination of gemcitabine and ganitumab, a monoclonal antibody against IGF-1R, showed a significant clinical response in a phase 2 randomized trial [28], but unfortunately this combination did not show any clinical benefit in phase 3 evaluation [29]. Recently, a clinical study demonstrated a correlation between IGF-1R signaling and tumor aggressiveness in PDAC patients [15], and increased exposure to ganitumab was found to be associated with improved overall survival and progression free survival in metastatic PDAC [30].…”
Section: Introductionmentioning
confidence: 99%
“…In a phase III trial assessing ganitumab in combination with gemcitabine, the study closed early based on a pre-planned futility analysis. The median overall survival was 7.1 mo in the maximum dose ganitumab arm vs. 7.2 mo in the placebo arm (HR 0.97, P=0.397) (98).…”
Section: Igfr Pathway Inhibitorsmentioning
confidence: 94%
“…It has been shown to delay growth of human pancreatic cancer and neuroblastoma cells[44, 53]. Ganitumab, an Ab targeted to IGF-1R, was well tolerated in a phase III trial but failed to improve OS in combination with gemcitabine compared to gemcitabine alone in patient s with metastatic pancreatic cancer[54]. Dalotuzumab is a humanized IGF-1R monoclonal antibody that selectively binds to IGF-IR and blocks receptor autophosphorylation and cell proliferation in vitro.…”
Section: Signaling Disruptionmentioning
confidence: 99%